Case Report: Successful Treatment of Alopecia Universalis With Tofacitinib and Increased Cytokine Levels: Normal Therapeutic Reaction or Danger Signal? - Yu, Ling; Yu, Huiqian; Zhang, Shuai; Hao, Yanzhao; Zhang, Shoumin (Frontiers in Immunology, 2022)
Alopecia universalis (AU) is an autoimmune disorder characterized by non-scarring hair loss in the scalp, eyebrows and beard, and nearly the entire body, negatively affecting patient prognosis. Available treatments are usually unsatisfactory. The autoimmune attacks of hair follicles induced by CD8+ T cells and the collapse of hair follicle immune privilege are believed to be the leading causes of AU. Additionally, interferon(IFN)-γ plays an important role in triggering the collapse of hair follicle immune privilege and impairing hair follicle stem cells. Furthermore, the upregulation of Janus kinase(JAK)3 and phospho-signal transducer and activator of transcription (pSTAT)3/ STAT1 in alopecia areata patients suggest that JAK inhibitors can be a potentially promising choice for AU patients for the reason that JAK inhibitors can interfere with JAK-STAT signaling pathways and inhibit IFN-γ. Herein, we report a case of AU successfully treated with tofacitinib. However, this beneficial response in the patient was accompanied by a remarkable increase in peripheral blood cytokine levels during tofacitinib treatment.